Issues and Problems in Malaysian Contemporary Visual Arts - Mohamad Faizuan Mat; Mohamad Nasir Baharuddin (ITB Journal Publisher, LPPM ITB, 2016)
In Malaysia, there is a question in term of intellectualism activities in the context of visual epistemology. Therefore, this paper revealed the problems that linger in the Malaysian contemporary visual art scene. In fact, Malaysian contemporary artists appear to have insufficient intellectualism values and less discourse activities. The lacks of scholars in the field of visual arts create a gap in the visual arts scene in Malaysia. The question of this study was to uncover the main problems in Malaysian visual arts that led to the problem of art intellectual development. In addition, this paper presents the awareness of the valuable contributions in the intellectual development that able to enhance the communication in the art object.Keywords: art knowledge; art object; contemporary art; interpretation; perception;